Semantic Web for Virtual University Using XML and Relational Database (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper a development of virtual university semantic web service is focused. This approach uses XML, relational database and development of a web application to store, retrieve, and transfer operative notes between database and XML file. To provide an additional management features for this suggested approach, a proposed web application is designed to be intelligent. In addition, the system analysis phase contains a detailed study of various operations performed internally or externally by running system. Activities of the system analysis phase follow iterative approaches where the deliverable is refined in incremental steps.Â  In the system design phase, Entity-relationship (ER diagram) and normalization are used to design a database using MySQL. The XML format for operative data is designed using Document Type Declaration (DTD) and XML schema. The interchange model is designed using context diagram, dataflow diagram, system flowchart, and process specification. The proposed web application is developed using VB.Net Interface and VRML modeling 3dmax. Finally, the proposed approach files are transmitted in XML, PDF and HTML formats.